Effect of litter size, milk replacer and housing on production results of hyper-prolific sows. (25th April 2020) - Kobek-Kjeldager, C.; Moustsen, V. A.; Theil, P. K.; Pedersen, L. J.
Abstract : The modern hyper-prolific sow gives birth to more piglets than she has functional teats (in the following called supernumerary piglets). The aim of the present study was (1) to investigate the production consequences of hyper-prolific sows rearing supernumerary piglets equal to the mean live-born litter size, and (2) investigate whether potential negative effects on survival and growth could be alleviated by providing access to milk replacer and/or providing easier access to the udder (by loose housing). At day 1 (D1) postpartum ( pp ), 93 litters were standardised to 14 or 17 piglets (LS14/LS17) after which no piglets were moved between sows leading to decreased litter size if piglets died. Litters were provided with or without milk replacer in milk cups (+MILK/−MILK), and sows were either crated or loose housed (CRATE/LOOSE) in a 2 × 2 × 2 factorial design. Piglet mortality was higher in LS17 compared to LS14 ( P < 0.01; OR = 2.0), higher in −MILK compared to +MILK ( P = 0.01; OR = 1.2) and higher in LOOSE compared to CRATE ( P = 0.02; OR = 1.8). This study showed that sow rearing of supernumerary piglets while supplying with milk replacer can increase piglet survival. It also showed that early mortality before piglets learned to drink milk replacer posed a challenge using this automatic milk replacer system. An interaction between access to milk replacer and the standardised litter size D1 affected litter weight ( P < 0.01) and piglet weight day 28 (D28) ( P = 0.03). The highest litter weight D28 was found in LS17 +MILK ( P < 0.01) but with a lower individual piglet weight than in LS14 −MILK. Piglet weight D28 was higher in LS14 −MILK compared to LS17 regardless of access to milk replacer. Heterogeneity in piglet weight within litters D28 was larger in LS17 ( P = 0.03) but could be reduced with +MILK in CRATE ( P < 0.01). No effects were found on sow weight loss and feed intake ( P > 0.05). In conclusion, the results showed that sows cannot rear the supernumerary piglets without further management interventions to reduce mortality. Supplying supernumerary piglets equal to the mean live-born litter size of hyper-prolific sows with milk replacer can from results of this study be an alternative strategy to the use of nurse sows.